Técnicas de resgate e propagação vegetativa de híbridos de Corymbia spp. por estaquia - Souza, Hendrick da Costa de (2023)
The general objective of this research was to study techniques for vegetative rescue and propagation by cuttings of Corymbia spp. The first chapter aimed to evaluate vegetative rescue methods for inducing epicormic shoots and applying different concentrations of indolebutyric acid (IBA) in cuttings of hybrid progenies of Corymbia spp. The second chapter aimed to analyze different concentrations and forms of application of IBA, rooting environments and type of cuttings in a clone of C. torelliana x C. citriodora. In the first phase, three rescue techniques were evaluated (girdling, stump at 15 and 90 cm from the ground) combined with and without exposure of the lignotubers, evaluating the production of shoots and cuttings in five collections in the field. The rooting of cuttings from rescue techniques was evaluated, in addition to the effect of different concentrations of IBA (zero; 1500; 3000 and 4500 mg L-1) on the cutting. In the second phase, three experiments were conducted, and in the first two different concentrations of IBA were evaluated (zero, 4500, 6500, 8500 and 10500 mg L-1 / mg kg-1), in liquid and powder form, in two rooting environments (CV1 and CV2). In the third experiment, different types of cuttings (intermediate and apical) were analyzed with and without a 50% reduction in leaf area. Anatomical analyzes were conducted with material from CV1 to characterize adventitious rhizogenesis and verify possible anatomical barriers to rooting. The rescue technique, using the strain at 15 cm from the ground and exposing the lignotubers (strain 15/CE), increased the production of shoots and obtaining cuttings. In the seedling production phase, it was found that the cuttings obtained from the strain 15/CE technique showed higher percentages of cuttings with leaves (23.4%), rooting (23.4%) and callogenesis (46.60%). The use of IBA at a concentration of 4500 mg L-1 provided higher percentages of survival (76%), cuttings with leaves (72%) and rooting (52%) for Corymbia hybrid progenies. In the CV1 environment, high cutting mortality was observed (61.26%), due to the high humidity in the greenhouse (91.53%) and mild temperature (18.17 ºC) in the winter period, making rooting unfeasible. In the CV2 environment, with the use of IBA powder at an average concentration of 4000 mg kg-1, greater survival (93.31%), leaf retention (89%) and superior morphological development (height, dry mass of the aerial, total dry mass and leaf area) in the rooting phase. No anatomical barrier to adventitious rooting was observed, with a connection between the root primordium and the vascular tissue. The presence of phenolic compounds was found in the cuttings. The intermediate cutting with a 50% reduction in leaf area proved to be the most efficient propagule in the clone cutting. In general, the best vegetative rescue technique in Corymbia spp. is strain 15/CE, using intermediate cuttings with a 50% reduction in leaf area and application of IBA powder at a concentration of 4000 mg kg-1. Managing environmental conditions in the rooting environment is essential to enhance the success of vegetative propagation by cuttings of C. torelliana x C. citriodora.